2022
DOI: 10.3390/genes13071211
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Effect of Metformin and Everolimus on Mitochondrial Dynamics of Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) frequently recurs or metastasizes after surgical resection. Everolimus, an mTOR inhibitor, is used as a second-line treatment, but the response of RCC to everolimus is insufficient. Metformin is an antidiabetic drug; recent reports have indicated its anti-cancer effects in various cancers, and it is known to have synergistic effects with other drugs. We investigated the possibility of coadministering everolimus and metformin as an effective treatment for RCC. RCC cells treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…To further explore the potential value of the NF-κB pathway in the clinical treatment of patients with KIRC, we plotted box plots based on drug susceptibility predictions in the GDSC database to determine the effect of the NF-κB pathway on IC50 of 12 commonly renal carcinoma targeted drugs. In these drugs, sorafenib is the first targeted multi-kinase inhibitor and first-line chemical drug approved for the treatment of RCC, which blocks formation of tumor neovascularization and directly inhibits the proliferation of RCC cells by blocking RAF/MEK/ERK signaling pathway [ 24 ]; Sunitinib inhibits the development of tumor-associated vascular disorders and affects the infiltration of immune cells such as regulatory T cells and macrophages [ 25 ]; metformin inhibits RCC cell viability (including cell migration and invasion) and increases apoptosis by disrupting mitochondrial dynamics [ 26 ]; other drugs also show different mechanisms of action in cancer suppression. We found that sensitivity to sorafenib, gefitinib, and metformin was higher in the downregulated NF-κB group (C3) but not in the upregulated NF-κB group (C2).…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the potential value of the NF-κB pathway in the clinical treatment of patients with KIRC, we plotted box plots based on drug susceptibility predictions in the GDSC database to determine the effect of the NF-κB pathway on IC50 of 12 commonly renal carcinoma targeted drugs. In these drugs, sorafenib is the first targeted multi-kinase inhibitor and first-line chemical drug approved for the treatment of RCC, which blocks formation of tumor neovascularization and directly inhibits the proliferation of RCC cells by blocking RAF/MEK/ERK signaling pathway [ 24 ]; Sunitinib inhibits the development of tumor-associated vascular disorders and affects the infiltration of immune cells such as regulatory T cells and macrophages [ 25 ]; metformin inhibits RCC cell viability (including cell migration and invasion) and increases apoptosis by disrupting mitochondrial dynamics [ 26 ]; other drugs also show different mechanisms of action in cancer suppression. We found that sensitivity to sorafenib, gefitinib, and metformin was higher in the downregulated NF-κB group (C3) but not in the upregulated NF-κB group (C2).…”
Section: Resultsmentioning
confidence: 99%